Synthesis, characterization and thermochemistry of piperazine complexes of bivalent metal bromides - Dunstan, Pedro Oliver; Khan, Abdul Majeed (European Journal of Chemistry, 2013)
Complexes of bivalent metal bromides with piperazine were prepared in hot ethanol solution. They have the general formula: [MBr2(pipz)n], where M = Mn(II), Fe(II), Co(II), Ni(II), Cu(II) or Zn(II); pipz = piperazine; n = 1 or 1.5. They were characterized by melting point measurements, elemental analysis, TG/DTG-DSC curves, IR and electronic spectroscopy. The enthalpies of solution of the complexes, salts and ligand were measured by thermo-chemical cycles and several thermochemical parameters were determined. The mean standard enthalpies of the metal-nitrogen coordinated bonds and the enthalpies of gaseous complex formation were also determined.